Kajian Analisis Pelafalan Fenomenologi Bunyi Segmental Di Kecamatan Baros Kabupaten Pandeglang - juanto, ade; basrowi; Vidya; dewi, raviena; sopiah; soleha, siti; farihah, iftahul; a'isyah putri, adinda (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This research was conducted to better understand segmental language sound analysis. The use of language in highland and lowland areas definitely has differences in terms of the loudness and softness of the sounds spoken, the pitch of the sounds, the length and shortness of the sounds, and so on. In the pronunciation of these sounds, the lowland and highland areas have differences in terms of segmental pronunciation sounds. This research method uses a methodological approach and qualitative research methods. The methodological approach consists of a qualitative descriptive approach, while the qualitative approach in research consists of a dialectological approach, especially dialect geography. Dialectological research is basically language research that is systematic, empirical and critical of the target object in the form of speech sounds. The use of this qualitative method is to qualitatively describe perceptions about the use and pronunciation of language sounds in the highlands and lowlands, which are used by people living in these areas, using sound usage (segmental) analysis. From the results of research and data, it is proven that the use of segmental language sounds from the lowlands and highlands proves that high and low sounds do occur in the Pandeglang area, Baros. Based on the results of the analysis above, the pronunciation of segmental sounds in this analysis has found data that in everyday conversation 100% proves that segmental sounds are applied in life, and has found language sounds in daily life conversations such as vowels, consonants, diphthongs. , clusters, as well as the high and low levels of sound produced. Dari hasil penelitian dan data-data yang dilakukan membuktikan bahwa penggunaan bunyi bahasa segmental dari dataran rendah dan dataran tinggi membuktikan, tinggi rendahnya bunyi memang terjadi di daerah Pandeglang, Baros. Berdasarkan hasil analisis diatas pelafalan bunyi segmental dalam analisis ini telah menemukan data-data bahwa dalam percakapan sehari-hari 100% membuktikan bahwa bunyi segmental di terapkan dalam kehidupan, serta telah menemukan bunyi bahasa dalam percakapan kehidupan sehari-hari seperti bunyi vokal, konsonan, diftong, kluster, serta tinggi rendahnya bunyi yang dihasilkan.